Perceived Racial Discrimination and DNA Methylation Among African American Women in the InterGEN Study. Issue 2 (March 2018) - de Mendoza, Veronica Barcelona; Huang, Yunfeng; Crusto, Cindy A.; Sun, Yan V.; Taylor, Jacquelyn Y.
Introduction: Experiences of racial discrimination have been associated with poor health outcomes. Little is known, however, about how perceived racial discrimination influences DNA methylation (DNAm) among African Americans (AAs). We examined the association of experiences of discrimination with DNAm among AA women in the Intergenerational Impact of Genetic and Psychological Factors on Blood Pressure (InterGEN) study. Methods: The InterGEN study examines the effects of genetic and psychological factors on blood pressure among AA women and their children. Measures include the Major Life Discrimination (MLD) and the Race-Related Events (RES) scales. In the present analysis, we examined discrimination and DNAm at baseline in the InterGEN study. The 850K EPIC Illumina BeadChip was used for evaluating DNAm in this epigenome-wide association study (EWAS). Results: One hundred and fifty-two women contributed data for the RES-EWAS analysis and 147 for the MLD-EWAS analysis. Most were 30–39 years old, nonsmokers, had some college education, and had incomes <US$15, 000/year. After controlling for age, smoking, and cell composition, MLD was significantly associated with DNAm at nine CpG (regions of DNA where a cytosine nucleotide is followed by a guanine nucleotide) sites (false discovery rate [FDR]-corrected p < .05). For the RES-EWAS analysis, no DNAm sites passed the epigenome-wide significance level after genomic control, though suggestive associations were observed at CpG sites after genomic control (raw p < 10 −5 ). Conclusion: We observed significant epigenetic associations between disease-associated genes (e.g., schizophrenia, bipolar disorder, and asthma) and perceived discrimination as measured by the MLD Scale. Future health disparities research should include epigenetics in high-risk populations to elucidate functional consequences induced by the psychosocial environment.